E-Commerce Information System Design in Web-Based UD Anggun Shoe Store - Billy Al Ghazian Ramadhan Akbar; Ika Ratna Indra Astutik (Universitas Muhammadiyah Sidoarjo, 2022)
E-commerce or online shopping is a concept that is quite developed in the internet world. The use of this system can benefit many aspects, including consumers, producers, and sellers. The information system is a combination of work procedures, information, staffing, and information technology that is organized to achieve organizational goals. Information systems have become an urgent need in all areas of life including business. One ofthe companies engaged in trading, namely the Anggun Shoe Store, really needs information system technology that provides sales data recap functions and sales profit reports because consumers have difficulty getting detailed information on product specifications offered and employees find it difficult to offer products sold to consumers outside the city. Web-Based E-Commerce Information System Design (Anggun Shoe Store). An information system is needed by this company as well as other companies that run a similar business model, to facilitate sales reporting sothat their business can be measured. This system also makes it easier for business owners to view daily sales reports so they can determine marketing strategies for the future.